Dental students as smoking cessation counsellors: Patients' and providers' perspective - Mohd Nor, Nor Azlida; Repen, Marvin Costher; Zakaria, Zakuan; Ab-Murat, Norintan; Saub, Roslan; Razak, Ishak Abdul (International Islamic University Malaysia, 2018)
Introduction: This study assesses dental students' and patients' perceptions on the role of dental students as smoking cessation counsellors as well as the patient's quit rate at the University of XX. Materials and methods: Self-administered questionnaires were distributed to all senior dental students (n=154) in XX University and telephone call interviews were conducted on their patients (n=169) who received smoking cessation counselling from September 2010 to June 2013. Results: Response rates for dental students and patients were 68.2% and 67.3% respectively. Most of the dental students in this study were females (72.3%) whereas the majority of patients were males (97.6%). An average of six months follow up indicated that 22.5% of patients had quit smoking, 65.3% reduced the number of cigarettes smoked and 6.5% had relapsed. About a third of patients surveyed (33.1%) believed that smoking cessation counselling was extremely helpful compared to what students perceived (5.7%, p<0.01). A higher percentage of patients (89.9%) rated the smoking cessation counselling performance as "excellent", as compared to students' rating (58.1%, p<0.01). The majority of the dental students and patients agreed that students should enquire about patients tobacco usage, information regarding the effects of smoking on oral health should be transmitted to patients and that quit smoking assistance should be offered. Conclusion: Smoking cessation counselling conducted by dental students seemed to be effective in assisting patients to reduce the number of cigarettes smoked and in quitting smoking. To some extent, both patients and students had positive attitudes towards smoking cessation counselling.